Synthesis of Oxazole, Oxazoline and Isoxazoline Derived Marine Natural Products: A Review - Tilvi, Supriya; S. Singh, Keisham (Current Organic Chemistry, 2016)
Secondary metabolites containing oxazole, oxazoline and isoxazoline ring skeletons are widely distributed in both marine and terrestrial organisms. They possess significant biological activities such as anti-tumor, antibacterial, anti-viral, anti-malarial and immunosuppressive. The complexity in the molecular structures coupled with their wide biological properties, has attracted the attention of many synthetic and natural product chemists. The introduction of multifunctional substituents and the construction of stereo-centers were considered as major challenges and obstacles in developing synthetic protocol for these classes of compounds. Few review articles on the total synthesis of oxazole contaning marine natural products namely bengazoles, phorboxazole, pseudopteroxazoles, hennoxazole and cyclopeptide have been reported till date. However, these reviews omitted the discussion on isolation and biological activities. In this review, we present the brief account on isolation, relevant biological activities and a recent development on the total synthesis of marine natural products containing oxazole, oxazoline and isoxazoline ring skeletons reported till 2014.
Keywords: total synthesis